Tradición clásica en el Laurel de Apolo de Lope de Vega - López Fonseca, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2010)
The aim of this article, which begins with an approach to the presence of classical culture in the works of Lope, is to present a study of the classical tradition in one of his lesser-known non-dramatic works, Laurel de Apolo, a narrative poem of didactic intent. prior to the study of the classical tradition, Lope de Vega is portrayed as a synthesis of the Renaissance and the Baroque periods, and the main characteristics of his non-dramatic works are outlined.